2013
DOI: 10.1021/ja405916q
|View full text |Cite
|
Sign up to set email alerts
|

Chemical Insight into the Emergence of Influenza Virus Strains That Are Resistant to Relenza

Abstract: A reagent panel containing ten 4-substituted 4-nitrophenyl α-D-sialosides and a second panel of the corresponding sialic acid glycals were synthesized and used to probe the inhibition mechanism for two neuraminidases, the N2 enzyme from influenza type A virus and the enzyme from Micromonospora viridifaciens. For the viral enzyme the logarithm of the inhibition constant (Ki) correlated with neither the logarithm of the catalytic efficiency (kcat/Km) nor catalytic proficiency (kcat/Km kun). These linear free ene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
43
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(43 citation statements)
references
References 30 publications
0
43
0
Order By: Relevance
“…It can be argued that a transition state mimicking inhibitor has the potential to provide potent inhibitors that should be resistant to mutations within the active site, as mutations that affect the ability of the inhibitor to bind should also affect the catalytic proficiency of the enzyme to similar degrees, resulting in loss of fitness for the virus. By making alterations in the structure of zanamivir at the 4-position and relating the effects of these changes upon inhibitor K I values to the equivalent changes to the substrate and their effect upon k cat / K M or K M Bennet and co-workers showed that zanamivir is not a transition state analogue and is better considered a ground state analogue [58 • ]. Notably, this is confluent with the observation that influenza strains resistant to zanamivir possess reduced binding avidity for this drug but still possess catalytic competence.…”
Section: Neuraminidases: Of Conformational Itineraries and Transitionmentioning
confidence: 99%
“…It can be argued that a transition state mimicking inhibitor has the potential to provide potent inhibitors that should be resistant to mutations within the active site, as mutations that affect the ability of the inhibitor to bind should also affect the catalytic proficiency of the enzyme to similar degrees, resulting in loss of fitness for the virus. By making alterations in the structure of zanamivir at the 4-position and relating the effects of these changes upon inhibitor K I values to the equivalent changes to the substrate and their effect upon k cat / K M or K M Bennet and co-workers showed that zanamivir is not a transition state analogue and is better considered a ground state analogue [58 • ]. Notably, this is confluent with the observation that influenza strains resistant to zanamivir possess reduced binding avidity for this drug but still possess catalytic competence.…”
Section: Neuraminidases: Of Conformational Itineraries and Transitionmentioning
confidence: 99%
“…1), which were designed to be reversible inhibitors that mimic the transition state structure of the sialic acid residue during the cleavage event by the neuraminidase enzyme, though careful subsequent evaluation showed they resemble ground states more than transition states. 3 Both drugs also take advantage of an anionic pocket observed in viral neuraminidase by incorporating either a guanidine or amine at C4 which imparts greater selectivity for viral over human neuraminidase. 4 Orally bioavailable oseltamivir has emerged at the leading antiviral treatment for influenza.…”
Section: Introductionmentioning
confidence: 99%
“…2527 Recently, Bennett and coworkers demonstrated that NA from virus or bacteria can accommodate a variety of groups at the 4 position of sialic acid, each molecule possessing a range of cleavage efficiency. 28 As a first step towards the development of highly specific substrates for influenza, we chose to introduce a methoxy group at the 4 and 7 positions of sialic acid and coupled it to the 3 or 6 hydroxyl group of d -galactose to establish proof of concept that these modifications lead to exclusive selectivity. We chose d -galactose instead of d -glucose for three reasons.…”
Section: Resultsmentioning
confidence: 99%